Infected lung bulla caused by Neisseria elongata: A case report. (2022) - Moriya, Tetsuji; Ohsumi, Akihiro; Tanizawa, Kiminobu; Matsumura, Yasufumi; Date, Hiroshi
Abstract: Neisseria elongata is a rod-shaped, Gram-negative, aerobic bacterium that is part of the normal oral bacterial flora. Although previously considered a non- or low-pathogenic organism, the development of bacterial detection methods has resulted in increased reports of N. elongata infections such that it has recently been recognized as a causative agent of serious infections even in non-immune-compromised patients. A 77-year-old man with rheumatoid arthritis-associated interstitial lung disease, chronic obstructive pulmonary disease, and diabetes mellitus was diagnosed with a nodule in the left lower lobe of his lung. Thoracoscopic wedge resection was performed, and pus was discharged from the specimen. Mass spectrometry of the swab culture revealed N. elongata . The patient's postoperative course was uneventful, and he was doing well without recurrence at 13 months after surgery. Since N. elongata is an oral bacterial flora, the patient consulted a local dentist, and decayed teeth were extracted. Most of the reported cases of serious N. elongata infections have described infective endocarditis. This is the first report of infected lung bulla due to N. elongata infection, which demonstrates a new pathogenicity.